The Roles of Buddhist Monks on Monastic Education in Mandalay, Myanmar - Zana, Ven. Thit (The Journal of International Buddhist Studies College, 2023)
Buddhism an education leads learners gain a proper knowledge to understand the reality of life. Buddhist education has focus on the three sources of education; 1) associate with good teacher or good friend, 2) listening or learning, 3) wise attention or thinking and practicing or training. Educational systems are dependent on the system of knowledge. This knowledge cannot operate without wisdom. And then, wisdom becomes the principal goal of the education system. The goal of Buddhist education is to attain “wisdom” (paññā). The Buddhist monks have many roles in Theravāda Buddhism and Mandalay, Myanmar society. The roles of Buddhist monk on education are associated with two kinds of duties (dhūra) which are grandadhura (teaching and learning to Tipiṭaka) and vipassanādhura (practicing and training to threefold training).